The effect of a single training session on cognition and mood in young adults – is there added value of a dual-task over a single-task paradigm?. Issue 1 (2nd January 2022) - Elkana, Odelia; Louzia-Timen, Rona; Kodesh, Einat; Levy, Sigal; Netz, Yael
ABSTRACT: The combination of simultaneous physical and cognitive training has rarely been assessed in young adults. Here we consider whether one dual-task cognitive and physical session was more effective than a single – cognitive or physical session in enhancing mood and cognitive functioning. In addition, we assessed whether habitual physical activity (PA) is a moderator of these training regimens. Individuals ( N = 116) aged 19–35 were randomly divided into four groups: physical exercise, cognitive exercise, combined physical-cognitive exercise, and control. Cognitive functioning was assessed by two tests of verbal fluency – phonemic fluency (PF) and semantic fluency (SF), and mood by the Profiles of Mood States (POMS). Level of PA was assessed by the International Physical Activity Questionnaire (IPAQ), and based on Metabolic Equivalents (METs) calculations, participants were divided into moderate- and high-level of PA. Three-way ANOVAs with repeated measures for the intervention groups and level of PA were conducted for each of the outcome measures – PF, SF, and POMS, followed by post-hoc comparisons. Results indicated that for those who engage in moderate-level PA, a session of combined physical and cognitive exercise is preferable over only physical or only cognitive, as the combined exercise may benefit both PF and mood. For high-level PA, combined exercise is not a stimulator for verbal fluency or for mood. Physical exercise as a single task is efficient in enhancing mood in those who engage in both moderate and high-level habitual PA. Further studies are recommended to explore the effect of simultaneously performed physical and cognitive exercise in young adults.